Experimental and thermodynamic study of the role of titanium in the microstructural and thermal properties of cast Ni–Cr–C–Ti alloys. (March 2017) - Berthod, Patrice; Kretz, Estelle; Allègre, Floriane
Abstract: Three compositions of the Ni–25Cr–0.25 or 0.50C–1 or 2Ti-type were studied by thermodynamic calculations for anticipating their melting temperature ranges and their microstructures at 1200 °C. In parallel the corresponding alloys were synthesized by classical foundry and subjected to Differential Thermal Analysis and exposures at 1200 °C followed by metallographic characterization. Calculations and experiments are globally consistent concerning the melting range temperatures, the microstructures in the as-cast state and after aging at 1200 °C. Good agreement was also found concerning the carbides fractions and the matrixes' chemical compositions.